Predicting multi-wavelength properties of Lyman break galaxies with GalICS - Blaizot, J; Guiderdoni, B; Devriendt, J; Bouchet, F; Hatton, S (2003)
GalICS (for GALaxies In Cosmological Simulations) is a model of hierarchical galaxy formation which combines high resolution numerical simulations for the dark matter component with semi-analytic prescriptions for the baryonic matter. It provides us with an explicit cosmological framework to analyse observations of distant galaxies, and to understand how they evolve to become local galaxies. We use GalICS to build multi-wavelength mock galaxy catalogues which include clustering properties. We can compare them to the sample of Lyman Break Galaxies at z=3 ( Steidel et al., 1996), and to deep sub-mm surveys. The predictions of the model will be detailed, and show a good agreement with the available data.